2007
DOI: 10.1007/s00101-007-1253-2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Trauma Life Support®

Abstract: Advanced Trauma Life Support (ATLS) is a concept for rapid initial assessment and primary management of an injured patient, starting at the time of injury and continuing through initial assessment, lifesaving interventions, re-evaluation, stabilization and, when needed, transfer to a trauma centre. Despite some shortcomings, it is the only standardized concept for emergency room management, which is internationally accepted. Because of its simple and clear structure, it is flexible and can be universally integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Hierbei sollten das Verletzungsmuster wie auch die Verletzungsschwere möglichst genau eingeschätzt werden, um daraus differenzierte Maßnahmen ableiten zu können. Insbesondere in der Akutphase steht die Stabilisierung der Vitalparameter im Vordergrund, sodass u. U. ein erhöhtes Risiko besteht, Traumafolgen zu übersehen oder fehleinzuschätzen [12]. Ziel der prähospitalen Einschätzung sollte es sein, die zur Verfügung stehenden Ressourcen optimal und zeitgerecht zu nutzen [17].…”
Section: Hintergrundunclassified
“…Hierbei sollten das Verletzungsmuster wie auch die Verletzungsschwere möglichst genau eingeschätzt werden, um daraus differenzierte Maßnahmen ableiten zu können. Insbesondere in der Akutphase steht die Stabilisierung der Vitalparameter im Vordergrund, sodass u. U. ein erhöhtes Risiko besteht, Traumafolgen zu übersehen oder fehleinzuschätzen [12]. Ziel der prähospitalen Einschätzung sollte es sein, die zur Verfügung stehenden Ressourcen optimal und zeitgerecht zu nutzen [17].…”
Section: Hintergrundunclassified
“…Münzberg et al showed that since 2003, ATLS has performed with high ratings based on evaluation by the participants [11]. Based on the “lowest common denominator”, ATLS is a concept for training the physicians dealing with severe injured patients in the emergency departments in Germany [13]. Ruchholtz et al showed in the 1990s that procedures based on the guidelines could improve the care of emergency room patients [14].…”
Section: Introductionmentioning
confidence: 99%